Fashionable dilemmas. Issue 1 (22nd December 2011) - Williams, Austin
Continuing the approach he developed in his book, The Enemies of Progress: The Dangers of Sustainability with regards to design, Austin Williams takes to task the emerging ethical and sustainability dogma in the area of fashion. While acknowledging the importance of the issues addressed by the rhetoric of ethics, per se, he takes issue with industries which employ it as a marketing strategy and as a platform to chide the less industrially developed countries. He critiques the attempt to use sustainability arguments in order to block the underdeveloped world from sharing the fortunes of the developed world's consumption levels. He challenges those who seek to address global problems through the prism of ethics: by blaming individual consumers, or by absolving their guilt through selective purchases. More generally he questions ethical fashion's self-appointed authority to moralize and in particular to impose on the underdeveloped world the equation that environmental concerns should take priority over poverty alleviation and human development.